PENGARUH KERAGAMAN ANGGOTA DEWAN DAN KARAKTERISTIK PERUSAHAAN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN NONKEUANGAN - Ruth Kartika Nauli; Aries Jonathan (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
The purpose of this study is to determine the effect of the diversity of board members and company characteristics on earnings management in the company. Generally, investors use income statement to evaluate the company's performance because they think that the company's profit reflects the company's performance. Therefore, there are often cases of manipulation of company profits by reporting profits that are not in accordance with the actual conditions of the company. This study uses a sample of non-financial companies listed on the Indonesia Stock Exchange from year 2018 until year 2020. The method used in selecting the sample is purposive sampling method with a total sample of 327 companies. Earnings management is proxied using discretionary accruals. Audit quality, company losses, and gender diversity of board members use dummy variable. Size of the company uses the natural logarithm. The age of the company uses logarithms in its measurement. Firm financial leverage and age diversity are measured using a ratio scale. The results of this study indicate that the age of the company and the company's losses have an influence on earnings management. However, firm size, firm financial leverage, audit quality, gender diversity of board members, and age diversity of board members have no effect on earnings management.